KINERJA PEMERINTAH DAERAH DALAM MENSOSIALISASIKAN WAWASAN KEBANGSAAN DI SULAWESI UTARA (STUDI KASUS DI BADAN KESATUAN BANGSA DAN POLITIK PROVINSI SULAWESI UTARA) - Jegiftha V. P. P Lumettu; Agustinus B. Pati; Johny P. Lengkong (AGRI-SOSIOEKONOMI, 2021)
This research aims to find out why the performance of the local government in socializing the national insight is not yet optimal. This research used descriptive qualitative research methods to provide a clear picture of a phenomenon or social reality relating to the problem under study. The results of this research shows that the process of implementing the socialization of national insight has been going well, but after being affected by the Covid-19 outbreak, â€œKesbangpoldaâ€ experienced budget problems, because the budget that should have been used for theÂ  socialization was shifted to handling Covid-19, hence â€œKesbangpoldaâ€ couldÂ  conduct only 3 activities of the 20 annual activities , and even then it is only done online which isÂ  considered ineffective to increase understanding of national insight . Thus, it is concluded that the performance of the National Unity and Political Agency of North Sulawesi Province is poor, because it only carried out 3 activities throughout 2020. For this reason, it is recommended that the North Sulawesi Provincial Political and National Unity Agency innovate the implementation of its socialization.